Peningkatan Pemahaman Peserta Didik tentang Materi Bangun Datar dengan Menggunakan Media Powerpoint Interaktif Berbasis Aplikasi Canva pada Mata Pelajaran Matematika Kelas 1 SDN 6 Cakranegara Tahun Pelajaran 2022-2023 - Wulandari, Dhea Rizki; Intiana, Siti Rohana Hariana; Najat, Safinatun (Lembaga Yasin AlSys, 2023)
This research applies learning using interactive PowerPoint media from the Canva application to the mathematics subject of plane figures so as to help students understand and remember the material being taught. The aim of this research is: 1) to describe how to apply interactive PowerPoint learning media based on the Canva application in mathematics learning on plane figures, class I at SDN 6 Cakranegara. 2) describe the increase in success in implementing interactive PowerPoint learning media from the Canva application in mathematics learning on plane material, class I SDN 6 Cakranegara. This research procedure was carried out in two cycles, each cycle having 4 stages, namely planning, acting, observing and reflecting. This research was conducted at SDN 6 Cakranegara with a total of 34 participants. The data collection techniques used are observation and tests. Based on the results of research on teacher activities, student activities and student learning outcomes have improved for the better. The research results show: 1) the application of interactive PowerPoint media based on the Canva application in mathematics learning on plane material shows an average percentage of completeness of 70.58%, when compared to before the application of the media which was 20.58%.